Unveiling the pathogenic mechanisms of polyethylene terephthalate-microplastic-driven osteoarthritis and rheumatoid arthritis: PTGS2 signaling hub-oriented toxicity profiling - Jingkai Di; Shuang Wang; Lujia Liu; Keying Rong; Zijian Guo; Yingda Qin; Feida Wang; Chuan Xiang (Ecotoxicology and Environmental Safety)
In recent years, health problems caused by microplastics (MPs) have attracted much attention. The pathogenic mechanisms of them in osteoarthritis (OA) and rheumatoid arthritis (RA) are still unclear and urgently need in-depth exploration. The targets related to OA and RA of Polyethylene Terephthalate (PET) were extracted from databases such as PubChem. Additionally, investigations into potential mechanisms were carried out through the utilization of Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analyses. Furthermore, six algorithms such as Closeness and the ROC curve were used to further screen the target proteins with high correlation. The stability of the interaction between the target protein and PET-MPs was verified by leveraging molecular docking and molecular dynamics (MD) simulations. Western blot (WB) and quantitative real-time polymerase chain reaction (qRT-PCR) experiments were conducted to verify the predicted results. The study identified 59 potential PET targets related to OA and 53 targets related to RA. Among them, biological processes such as γ-aminobutyric acid (GABA) and neural membrane potential regulation, as well as C-type lectin receptors and the neural active ligand-receptor interaction pathway were enriched significantly. In addition, different biological processes and signaling pathways specifically affect the processes of OA and RA. After further screening, two proteins such as AKT1 and four proteins such as NR3C1 have relatively high predictive values in OA and RA respectively. Among them, PTGS2 and PET-MPs are strongly correlated targets causing injuries in OA and RA. The in vitro experiments further confirmed that PET-MPs significantly increased the expression of PTGS2 during the progression of OA and RA. This study clarified for the first time the specific mechanisms and targets of PET-MPs in inducing OA and RA, providing a theoretical basis and technical reference for PET-MPs-related diseases.